Improving antimicrobial use among health workers in first-level facilities: results from the Multi-Country Evaluation of the Integrated Management of Childhood Illness strategy - Eleanor Gouws; Jennifer Bryce; Jean-Pierre Habicht; João Amaral; George Pariyo; Joanna Armstrong Schellenberg; Olivier Fontaine (Bulletin of the World Health Organization, 2004)
OBJECTIVE: The objective of this study was to assess the effect of Integrated Management of Childhood Illness (IMCI) case management training on the use of antimicrobial drugs among health-care workers treating young children at first-level facilities. Antimicrobial drugs are an essential child-survival intervention. Ensuring that children younger than five who need these drugs receive them promptly and correctly can save their lives. Prescribing these drugs only when necessary and ensuring that those who receive them complete the full course can slow the development of antimicrobial resistance. METHODS: Data collected through observation-based surveys in randomly selected first-level health facilities in Brazil, Uganda and the United Republic of Tanzania were statistically analysed. The surveys were carried out as part of the multi-country evaluation of IMCI effectiveness, cost and impact (MCE). FINDINGS: Results from three MCE sites show that children receiving care from health workers trained in IMCI are significantly more likely to receive correct prescriptions for antimicrobial drugs than those receiving care from workers not trained in IMCI. They are also more likely to receive the first dose of the drug before leaving the health facility, to have their caregiver advised how to administer the drug, and to have caregivers who are able to describe correctly how to give the drug at home as they leave the health facility. CONCLUSION: IMCI case management training is an effective intervention to improve the rational use of antimicrobial drugs for sick children visiting first-level health facilities in low-income and middle-income countries.